IMPORTANCE OF INTERNAL CONTROL FOR CREATIVE ACCOUNTING - Azira Osmanovic\'; Damir Saric\' (Agora International Journal of Economical Sciences (AIJES), 2023)
Creative accounting enabled accountants to use accounting policies more flexibly. However, it was precisely this flexible application of accounting policies that led creative accounting to become synonymous with manipulative accounting in practice. Financial reports should reflect the actual state of business, but they are often subject to numerous manipulations. In order to prevent manipulations in financial reports, it is necessary for the company to have an established internal control system. In the research conducted through an online survey in Bosnia and Herzegovina, the connection between internal control and the use of creative accounting was investigated. The research confirmed two pre-set hypotheses that the use of creative accounting has an impact on the quality of financial reports, and that well-established internal control prevents to use of creative accounting.
Keywords: 330